STREAMLINING EMAIL AUTOMATION: SEAMLESS INTEGRATION OF AUTOMATION 360 WITH OUTLOOK AND POWER AUTOMATE CLOUD FLOWS FOR CONTINUOUS EMAIL MONITORING AND UNATTENDED BOT DEPLOYMENT - Sai Madhur Potturu, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2023)
This research paper explores the integration of Automation 360 platform with Outlook and Power Automate cloud flows to enable continuous monitoring of shared mailbox folders and deploy unattended bots in response to incoming emails. This integration is achieved by leveraging the A360 bot deploy API, allowing different systems to trigger bots. The paper outlines two monitoring and integration methods. The first approach involves setting up VBA code in Outlook to monitor shared mailbox folders and trigger the A360 bot deploy API. This ensures the deployment of unattended bots when emails arrive in designated folders. The second approach utilizes Power Automate cloud flows to monitor shared mailbox folders and deploy unattended bots using the A360 Bot deploy API.The integration of Outlook, Power Automate, and A360 provides several advantages, including timely responses to customer inquiries, improved automation communication, and increased efficiency in email-based processes. Moreover, it optimizes the usage of unattended bot runners, enabling the deployment of scalable and high ROI automation solutions on these runners.By following the outlined steps and leveraging the capabilities of these tools, organizations can streamline their email-based processes, enhance productivity, and achieve greater automation efficiency. The integration of A360 with Outlook and Power Automate provides a comprehensive solution for continuous email monitoring and efficient utilization of automation resources.